Symbole i mity memuarystyki „Mój księżycowy przyjaciel” Zinaidy Gippius - Łucewicz, Ludmiła (Studia Rossica Posnaniensia, 2012)
Ludmila Lutsevich’s article “The Symbols and Myths of the Discipline that Studies Memoirs: My Moon Friend by Zinaida Gippius” mentions the characteristic feature of the Russian emigrational discipline that studies memoirs. The feature combines the alloy of facts of real existence, objective characteristics and a realistic evaluation in combination with a fictional plot, subjective descriptions, predictions and talks. These combinations led to the creation of mythological concepts and interpretations. Based on one of Zinaida Gippius’ earliest memoirs, the author of the article studies her interpretation of Aleksandr Blok’s personality as a romantic myth about a poet.